Relationship between FSH Receptor’s Exon 10 Polymorphisms with IVF Results in Iranian Women - Maliheh Javadi-Arjmand; Elia Damavandi; Hamid Choobineh; Majid Kabuli; Mohsen Ghadami (پیاورد سلامت)
Background and Aim: Follicle stimulating glycoprotein hormone (FSH) exerts its functions through its receptor (FSHR). In women of reproductive age, this hormone causes the growth and development of follicles in the ovary during the follicular phase of the menstrual cycle. This hormone is widely used in the treatment of infertility. Several polymorphisms have been reported so far in the FSHR gene, which are effective in the ovarian response, but the FSHR gene has two very common single nucleotide polymorphisms at positions 680 and 307 in exon 10. One of them at position 307 changes the amino acid threonine to alanine and the other at position 680 changes asparagine to serine. The polymorphism at position 307 of exon 10 is in the extracellular region of the receptor and the binding site of the hormone, which can be affected in response to internal and external FSH stimulation. These two SNPs have been reported to be associated with various ovarian responses and IVF outcomes in different populations. Different studies have particularly focused on rs6166 (p. Asn680Ser), but this study was conducted to investigate the possible association between rs6166 and rs6165 (p. Thr307Ala) and the IVF outcome. Materials and Methods: After blood sampling and DNA extraction, the two polymorphisms in exon 10 of FSHR gene were analyzed using PCR-RFLP method in 120 women randomly assigned to two equal groups including IVF successful and IVF unsuccessful infertile women. The selection of patients to enter the study as well as the criteria for successful IVF are described in the text. In order to confirm the results, DNA sequencing was done for some selected samples. Finally, the results were analyzed using SPSS software. Results: No significant differences were found in either SNPs between successful IVF and unsuccessful IVF patients in allelic frequencies (P-value>0.05). Conclusion: Despite the different results of the studies conducted regarding the effect of FSHR gene polymorphisms (rs6165 and rs6166) in different populations, considering the lack of significant difference in the frequency of the above polymorphisms in the studied population, it is concluded that these two polymorphisms cannot be used to predict the outcome of IVF in Iranian infertile women.